The concept of murabbi in Muslim education with reference to selected teaching methods of the prophet Muhammad (ٍٍٍِSAW) - Badrasawi, Kamal J I; Preece, Abdul Shakour Duncan; Hashim, Che Noraini; Nik Abdullah, Nik Md. Saiful Azizi (IIUM Press, International Islamic University Malaysia, 2017)
The concept of education in Islam is markedly different from that seen from the secular Western viewpoint. For Muslims, teaching is considered as the noblest of professions, while the Prophet Muhammad (SAW) is known as the greatest educator of all time. The focus of this paper is to explore the meaning of the concept of murabbī (Muslim educator) and then to consider selected pedagogical practices of the Prophet Muhammad (SAW) which were used to educate the early Muslim community. It is hoped that the pragmatic and spiritual nature of his pedagogical practices will serve as an inspiration and role model for Muslim and non-Muslim teachers and educators today and in the future, inshallah.